Transformation of PAI Learning Assessment in the Era of Digital Artificial Intelligence: Challenges, Opportunities, and Pedagogical Implications - Asa Mega Nusantara; Aji Joko Budi Pramono (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The development of Artificial Intelligence (AI) in the era of digital transformation has prompted changes in the learning assessment system, including in Islamic Religious Education (PAI). This research aims to analyze the transformation of PAI learning assessment in the AI era, identify opportunities and challenges in its implementation, and examine its pedagogical implications on the learning process. The research uses the Systematic Literature Review (SLR) method with the PRISMA approach. Data was obtained from the databases of ERIC, Scopus, DOAJ, Garuda, and SINTA in the 2021–2025 publication range. Of the 298 articles identified, 18 articles met the inclusion criteria and were analyzed using thematic analysis. The results of the study show that the integration of AI in PAI assessment is able to increase the efficiency, objectivity, and personalization of assessments through the use of learning analytics, adaptive assessment, automated scoring, and digital learning platforms. AI also assists teachers in providing feedback more quickly and systematically. However, the implementation of AI still faces challenges in the form of low digital literacy, limited infrastructure, the risk of academic plagiarism, as well as ethical issues and the protection of student data. Therefore, the application of AI in PAI assessment needs to be directed at strengthening humanistic, ethical, and spiritual values according to the goals of Islamic education.